Unconventional Methods to convert Naphtha to Diesel - Madaan, Udit; Menon, Aditya Balraj; Goel, Arpit (Journal of Advanced Research in Petroleum Technology & Management, 2021)
The 21st century has made it imperative for the logistics and transportation industry to be entirely dependent on the efficiency of the fuel used. The solution that was provided was that of the use of diesel as a fuel. As the consumption of diesel is increasing exponentially, novel methods are an immediate need for its surplus production. In the light of fast depleting fossil fuels, we have to ensure the security of the cogs of the logistics and transportation industry by looking at unconventional methods for the production of diesel so that the industry runs smoothly in the future too. As the global energy demand increases, one of the major problems faced by the refineries is to meet higher diesel demand. Demand for diesel-powered vehicles has increased over time and has in turn led to increasing demand for diesel over gasoline. There is strong surplus of gasoline production than middle distillates, which include jet fuel, heating kerosene, and gas and diesel oils. Surplus production of these distillates is a priority. Also the opportunities to incorporate naphtha into the gasoline pool are continuing to decline day by day, as a result, naphtha is creating problem to the refineries. A solution to the aforementioned problem may be found in the form of dieselization process. Dieselization is commonly applied in oil refining industries to shift yields towards diesel by crude selection, low severity fluid catalytic cracker operation and increased hydrocracking and residue upgrading. In this article, emphasis is given to the ways to achieve an increase in diesel output using novel unconventional methods and moreover, a comparative analysis is done between the unconventional and conventional methods of production. Some of the conventional options that refineries consider are well known. But focus here is mainly on unconventional methods like blending of different components. The preparation of poly-diesel by Oligomerisation is also taken into account. Another option is using the Syngas obtained from Steam reforming naphtha unit to produce more middle distillates via Fischer-Tropsch process. We have also taken into account the use of olefin components (obtained from LPG and FCC light naphtha) using aromatic alkylation and later hydrogenating them to produce alkyl-cycloparaffins. Also, an indepth study is done on how increased diesel output can provide better energy security and this method is adapted to the Indian scenario.